MODEL OF IMPROVING COMPLIANCE IN TREATMENT OF PULMONARY TUBERCULOSIS PATIENTS THROUGH CADRES IN BAITUSSALAM DISTRICT - Ferdi Riansyah; Aina Fitri; Ristiani Ristiani; Reka Julia Utama; Fitria Fitria; Kartini Kartini; Ibrahim Ibrahim; Niswatul Khaira (Getsempena Health Science Journal, 2025)
Various models and intervention strategies have been developed by various researchers to support the control and compliance of TB treatment and other infectious diseases. This study aims to produce a formulation of a model for increasing compliance of TB patient treatment as an important part of achieving TB cure and elimination in Baitussalam District, Aceh Besar. This study uses a qualitative research design with a phenomenological approach. The research informants numbered 16 people, consisting of one TB Puskesmas manager, five facilitator nurses, five TB patients (who are undergoing treatment, suspects, and former patients), and five families of patients. Data collection was carried out through in-depth interviews, focus group discussions (FGD), and document reviews. The results of the study found a phenomenon of minimal knowledge and ability of nurses in comprehensive peer group counseling services. The concept of the TB service model program that emphasizes all aspects of both physical and psychological TB patients is not yet strong. Formulation of a self-esteem model as an effort to increase the capacity of nurses to improve the quality of life of TB patients. This study produced a design of a self-esteem module to improve the ability of nurses in TB services through peer groups.